FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSLUSIF PADA IBU YANG MELAKSANAKAN IMD DI BPM KHAIRANI ASNITA TAHUN 2015 - Juliarti, Widya; Merlin, Atifa (Sistem Informasi, 2017)
Exclusive breastfeeding is the only breast milk given to infants without additional other liquids without solid food for six additional 6 months. Breastfed babies have a greater chance of early success exclusive breastfeeding. Based on preliminary studies in December 2015 in BPM Khairani Asnita, in the know of 20 people who gave birth to entirely successfully perform IMD but only 3-5 people who exclusively breastfed rest melanjutlan with formula. The purpose of this study to determine the factors associated with exclusive breastfeeding in mothers who carry BPM Khairani Asnita IMD in Riau Province in 2015. This type of research is analytic survey with cross sectional study design. The population is mothers delivered in BPM Khairani Asnita and do IMD with babies aged 16-12 months amounted to 60 m people. The sampling technique used is total sampling. Bivariate data analysis with test of chi-square test. Based on the results of the univariate analysis showed that the majority of mothers breastfeed as much as 56.7% exclusive. The results of the bivariate analysis pvalue values obtained for each variable with Î± 0.05 is for attitude p = 0.000, husband support the value of p = 0.004, p = success IMD 0,007, maternal age the value of p = 0.031. The conclusion of this study that the attitude of the mother, husband support, the success of IMD and the mothers age is a factor that affects exclusively breastfeeding mothers do IMD in BPM Khairani Asnita Year 2015. It is expected the next BPM Khairani Asnita able to reassure patients who visit or maternity there for can give only breast milk until the child is 6 months old, as well as explaining the benefits of exclusive breastfeeding for babies and mothers.